A novel sensor-embedded holding device for monitoring upper extremity functions - Ma, Charlie Chen; Mo, Pu-Chun; Hsu, Hsiu-Yun; Su, Fong-Chin (Frontiers in Bioengineering and Biotechnology, 2022)
There are several causes that can lead to functional weakness in the hands or upper extremities (UE), such as stroke, trauma, or aging. Therefore, evaluation and monitoring of UE rehabilitation have become essential. However, most traditional evaluation tools (TETs) and assessments required clinicians to assist or were limited to specific clinical settings. Several novel assessments might apply to wearable devices, yet those devices still need clinicians or caretakers to help with further tests. Thus, a novel UE assessment device that is user-friendly and requires minimum assistance would be needed. The cylindrical grasp is one of the common UE movements performed in daily life. Therefore, a cylindrical sensor-embedded holding device (SEHD) for training and monitoring was developed for a usability test within this research. The SEHD has 14 force sensors with an array designed to fit holding positions and one 6-axis inertial measurement unit (IMU) to monitor the grip strength, hand dexterity, acceleration, and angular velocity, respectively. Six younger adults, six healthy elderly persons, and three participants who had suffered from stroke participated in this study to see if the SEHD could be used as a reference to TETs. In the results where the persons’ correlation coefficient analyses were applied, forearm rotation smoothness and PPT showed a moderate negative correlation (r(16) = -0.724, p<0.01), and the finger independence showed a moderate negative correlation with PPT ( r(10) = -0.615, p<0.05). There was also a high positive correlation between the maximum pressing task and the Jamar dynamometer in maximum grip strength (r(16)= 0.821, p < 0.01). These outcomes suggest that the SEHD with simple movements could be applied as references for users to monitor their UE ability.